EXPRESSION PROFILE OF MICRORNAS IN SQUAMOUS CELL HEAD AND NECK CARCINOMA - Yu. A. Veryaskina; G. V. Kakurina; E. S. Zhuravlev; S. E. Titov; I. V. Kondakova; O. V. Cheremisina; D. A. Shishkin; I. F. Zhimulev; E. L. Choynzonov; N. N. Kolesnikov (Сибирский онкологический журнал, 2016)
Head and neck squamous cell carcinoma (HNSCC) is a highly aggressive disease with long asymptomatic course. New molecular prognostic markers are urgently needed to identify patients at high risk for developing lymph node metastasis. MicroRNAs (miRNAs) are a recently discovered class of small non-coding RNAs. Based on literature and our data, we have chosen 12 miRNAs (miRNA-21, -221, -222, -155, -205, -20a, -125b, -146b, -181b, -200a, -126, -451), involved in HNSCC carcinogenesis. Using real-time quantitative polymerase chain reaction analysis, we have shown a change in the expression miRNA in tumor tissue compared to unmodified tissue. Significant upregulation of five miRNAs: miRNA-21, -155, -181b, -126, -451 (p<0.05) has been shown in tumors. MiRNA-126 has been found to be highly expressed in metastasis tissue (p<0.05), and can be an important factor in understanding the processes of metastasis and development of a new prognostic marker.